Distribution evaluation of tacrolimus in the ascitic fluid of liver transplant recipients with liver cirrhosis by a sensitive ultra‐performance liquid chromatography‐tandem mass spectrometry method. Issue 2 (5th November 2021) - Yang, Na; Du, Yao; He, Jun; Ge, Jiajia; Wang, Min; Sun, Runbin; Zhu, Huaijun; Ge, Weihong
Abstract: Tacrolimus has a narrow therapeutic index and large individual differences in pharmacokinetics. The distribution of tacrolimus in ascitic fluid and its influence on whole‐blood tacrolimus were unclear. In this study, a sensitive ultra‐performance liquid chromatography‐tandem mass spectrometry method was established and validated for the quantification of tacrolimus in the ascitic fluid of liver transplant recipients. Chromatographic separation was achieved on an Agilent ZORBAX Eclipse Plus Phenyl‐Hexyl column (2.1 × 100 mm, 3.5 μm). Mass spectrometry was performed in multiple reaction monitoring conditions of transitions m/z 821.4→768.5 for tacrolimus. The concentrations of tacrolimus in the ascitic fluid range from 0.2 to 3.0 ng/mL, accounting for 1.19–31.87% of whole‐blood tacrolimus concentrations. A linear mixed model showed a statistically significant positive correlation between the steady‐state trough blood concentration of tacrolimus and the corresponding amount of tacrolimus excreted in the ascitic fluid for 24 consecutive hours, especially after normalization by daily dose per unit body weight. These data suggested that the distribution of tacrolimus in the ascitic fluid has great individual differences. The whole‐blood tacrolimus concentration, dose per unit body weight, and other confounding factors may contribute to the excretion of tacrolimus in ascitic fluid, but the influence of tacrolimus excretion in drained ascitic fluid on the whole‐blood tacrolimus concentration is negligible.